(3GdJHjGf aj Ydei GdeYGfi hGdHjGfs - (3GdMSjf Hf eMeO Hf YHO Gddg, TQa GdOjf GdpqWjHj,J (B743 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HSfGA eMGeOg ai SeGA GdeYGfi ef TehS GdHjGf CfLe hHOhQ s
(3BNQgG (B:s
(3Je GdcJGH hgh GdeSeiq s
(3HMhGTjgG GSJNQGLGJ deUWdMGJ HdGZjI HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B53s
Keywords: (3GdHdGZIs